PERANCANGAN APLIKASI SISTEM PENYEWAAN ONLINE BAJU ADAT - Syulfiani, Besse; Wafiah, Andi; Yunus, Mughaffir; Masnur (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Traditional dress rental in Indonesia is an important cultural element, often used for events such as weddings and cultural ceremonies. However, offline rental systems have limitations in terms of time and accessibility. This study aims to design an online traditional dress rental system application that addresses these limitations, focusing on user comfort and preferences. A quantitative approach was used in this research, involving a survey of 30 respondents who have experience or interest in traditional dress rental. The questionnaire was designed to identify user preferences, comfort in using the application, and desired features in the online rental system. The results indicate that the majority of respondents prefer online rental systems due to the ease of access and flexibility of time. Desired features include diverse payment methods, dress search filters based on type, size, and price, as well as real-time rental return notifications. This study contributes to the development of an effective online rental application that not only provides convenience for users but also supports the preservation of Indonesian culture. With this application, it is expected to enhance public accessibility to a variety of traditional dresses while introducing and preserving Indonesian cultural heritage through a digital platform.